Identification of Performance Variables For Design of Development Strategies Private Higher Education (Case Study, Indonesian Institute Of Technology) - abdul haris lahuddin (Liaison Journal of Engineering, 2023)
The purpose of this study is to obtain the characteristics of the dominant performance variables in relation to the development strategy of Private Higher Education (PTS). The expected output from the research results is a priority ranking of the most influential performance factors in the development strategy of the Indonesian Institute of Technology. In this study, the design of a development strategy was carried out using the Space Matrix analysis method and SWOT analysis to produce a Grand Strategy where the PTS-ITI strategic position lies in the Strengths Opportunities (aggressive strategy) position. Data processing uses factor analysis to identify the dominant performance variables, where there are 26 variables that are prioritized as a priority in implementing strategies so that the attainment of predetermined organizational goals can be more effective and successful. Keywords: Performance Variables, Factor Analysis, Space Matrix Analysis, SWOT, Grand Strategy.